PAULO FREIRE AT FARIA LIMA? CONTRIBUTIONS OF CRITICAL PEDAGOGY TO BRAZILIAN FINANCIAL LITERACY - Sameer El Khatib, Ahmed (2024)
The aim of this paper is to highlight the voices of teachers, the professionals who make curricular decisions, about the best way to provide critical financial literacy for their students, their assumptions, thoughts and experiences. Four research questions were formulated to achieve this objective, the main one being: How can critical, collaborative and dialogical financial literacy be facilitated to help students become critical citizens in light of Paulo Freire's contributions? We explore the concept of financial literacy from different perspectives and the literature on established national curricula for financial education from some countries around the world. Next, we seek theoretical support for a better understanding of critical pedagogy, through dialogue with authors such as Paulo Freire, Henry Giroux, Jürgen Habermas, Lev Vygotsky, Peter McLaren, Michael Apple, Antonia Darder and Ira Shor. The participants in this research were sixteen teachers from elementary schools I and II in the state of São Paulo, who demonstrated adherence to critical financial literacy practices, regardless of the subject taught. This is a qualitative study that adopts case study strategies, focus groups and deliberative research, to examine the beliefs, practices and life stories and narrative vignettes of the participants. The structures developed for critical financial literacy in terms of necessary skills, knowledge, pedagogical and curricular strategies are derived from the work of teachers in classrooms and not taken from a preconceived scheme in the literature, which indicates the promotion of citizenship oriented towards social and participatory justice. This thesis provides a dynamic conceptual framework developed for critical financial literacy, derived from the work of faculty and the views of Paulo Freire, which includes the translation of theory into praxis in line with Critical Pedagogy.